1989
DOI: 10.1016/s0022-5347(17)41020-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Treatment of Staghorn Calculi by Percutaneous Nephrolithotomy and Extracorporeal Shock Wave Lithotripsy

Abstract: The combined use of percutaneous nephrolithotomy and extracorporeal shock wave lithotripsy in patients with staghorn calculi has become an established treatment regimen. We evaluated the results of 90 staghorn calculi-bearing kidneys treated with such combination therapy after a mean follow-up of approximately 2 years. A total of 69 kidneys (76.7 per cent) became free of stones at some point after treatment. However, due to stone recurrence this number decreased to 55 kidneys (61.1 per cent) at the end of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…Though well popularized in the 1990s, combination therapy is less commonly used today due to its inferior results compared with PCNL monotherapy. For example, Schulze and colleagues [47] found that 76.7% patients were stone-free after combination therapy and this decreased to 61.1% at the end of follow-up due to recurrence. In a larger series of 343 cases of staghorn calculi by Lam and colleagues [48], PCNL alone achieved a stone-free rate of 91% compared with 78.1% to 79.1% with the combination approach.…”
Section: Combination Therapymentioning
confidence: 99%
“…Though well popularized in the 1990s, combination therapy is less commonly used today due to its inferior results compared with PCNL monotherapy. For example, Schulze and colleagues [47] found that 76.7% patients were stone-free after combination therapy and this decreased to 61.1% at the end of follow-up due to recurrence. In a larger series of 343 cases of staghorn calculi by Lam and colleagues [48], PCNL alone achieved a stone-free rate of 91% compared with 78.1% to 79.1% with the combination approach.…”
Section: Combination Therapymentioning
confidence: 99%
“…Extracorporeal shock wave lithotripsy (ESWL) is usually the treatment of choice for renal calculi £ 3 cm in size and percutaneous lithotripsy (PCNL) for larger stones [9][10][11][12][13][14][15][16]. However, in view of a recent report by Wilson et al showing pyelotomy as the safest available modality for treatment of renal lithiasis today, if pyelolithotomy could be performed by a minimally invasive technique, it might become the treatment of choice for such patients [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lechevallier et al [13] reported a higher likelihood for renal scar formation after ESWL sessions than after percutaneous nephrolithotomy [13]. Therefore, treatment options were directed towards a percutaneous surgical approach [14][15][16][17], open surgical approach [18], or various combinations of multi-modality treatments [8,19,20]. The decision to perform percutaneous nephrolithotomy in our patient rather than open surgery was influenced by a variety of factors.…”
Section: Discussionmentioning
confidence: 85%